Synthesis, bioactivity, and molecular docking of novel arylpiperazine derivatives as potential AR antagonists - Qi, Yueheng; Chen, Hong; Chen, Shijin; Shen, Jianliang; Li, Jingguo (Frontiers in Chemistry, 2022)
Prostate cancer is one of the malignant tumors and the second most common malignant tumor in men. Clinically used androgen receptor (AR)-targeted drugs can antagonize androgen and inhibit tumor growth, but these drugs can cause serious resistance problems. To develop novel AR antagonists, 22 kinds of arylpiperazine derivatives were designed and synthesized, and the derivatives 5, 8, 12, 19, 21, 22, 25, and 26 not only showed strong antagonistic potency (>55% inhibition) and binding affinities (IC50 <3 μM) to AR, but also showed stronger inhibitory activity to LNCaP cells versus PC-3 cells. Among them, the derivative 21 exhibited the highest binding affinity for AR (IC50 = 0.65 μM) and the highest antagonistic potency (76.2 % inhibition). Docking studies suggested that the derivative 21 primarily bound to AR-LBP site by the hydrophobic interactions. Overall, those results provided experimental methods for developing novel arylpiperazine derivatives as potent AR antagonists.